A development of performance assesment instrument for measuring cognitive and psychomotor competence on vinegar titration practicum - Mudrika Mudrika; Nahadi Nahadi; Kurnia Kurnia (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Implementation of learning can not be separated from the assessment activities. Performance assesment on chemical subjects are necessary to assess students' cognitive and psychomotor aspects. The purpose of this study is to produce a performance assesmen instrument that assesses the cognitive and psychomotor competence of a quality and tested titration practice of vinegar acids, in students of Class XI SMA. The research method used is Research and Development (R & D), which consists of (1) development stage of instrument making (2) validation and limited testing phase, and (3) application stage in the form of implementation in learning. Instruments in this study include validation sheet by expert team, assessment instrument sheet in the form of task and rubric, observation sheet and interview guide sheet. This research is only at the stage of instrument development . This research is essential to assist teachers in delivering quality student performance assesment instruments and can be used for further research in developing performance assesment instruments on other chemical concept